'Everyman's Land': the Second Christmas Truce, 1915. (1st December 2017) - Riley, Jonathon
Much has been written about the Christmas Truce of 1914, which was well covered by the press at the time; however, a second truce which occurred in December 1915, and which involved a Welsh battalion, was suppressed. Word of it began to surface in the early 1930s but it is only in the last few years, and during 2014 in particular, that a detailed account has emerged.